Muscarinic M1 and M2 receptors, fasting and seizure development in animals - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Muscarinic M-1 and M-2 receptors are widely distributed in the brain and contribute to various physiological and pathological functions. It is well known that enhancement of cholinergic activity produces convulsions in animals. Pilocarpine, the M-1 muscarinic receptor agonist, is commonly used to induce seizures in rodents. On the other hand it has been reported that fasted rats and mice pretreated with the M-1 and M-2 receptor antagonist atropine, scopolamine or biperiden develop convulsions after food intake indicating cholinergic hypoactivity as the underlying mechanism. This review will present pharmacological data for the M-1 and M-2 receptors in the brain and focus on the contrasting findings related to their contribution to convulsions.
Keywords: Seizures; receptors; muscarinic m1; muscarinic m2; SCOPOLAMINE-INDUCED CONVULSIONS; ACETYLCHOLINE-RECEPTORS; FASTED MICE; FOOD-INTAKE; PILOCARPINE MODEL; AGONISTS; BRAIN; LOCALIZATION; SUBTYPES; RELEASE